Children’s acceptance of xylitol- based foods - Lam M, Riedy CA, Coldwell SE, Milgrom P, Craig R (2000)
Daily consumption of xylitol (5–10 g/day) added to chewing gum and confectionary foods has been previously shown to prevent dental caries in children. Methods: Snack foods containing xylitol were developed and tested for acceptability in a convenience sample of 31 children ages 3 to 6 years. In order to mimic an after-meal snack, all children were tested during mid-morning, approximately 1 h after eating. Preference testing was based on the methodology of Birch et al. (J Nutr Educ, 1979; 11: 77–80).